MOF/polymer composite synthesized using a double solvent method offers enhanced water and CO2 adsorption properties. Issue 75 (3rd September 2018) - Peng, Li; Yang, Shuliang; Sun, Daniel T.; Asgari, Mehrdad; Queen, Wendy L.
Abstract : A double solvent method is for the first time used to synthesize polymer composites showing enhanced water and CO2 adsorption properties. Abstract : A double solvent method is for the first time used to synthesize a polymer composite that is constructed by a Ni-pyrazolate MOF and polydopamine (PDA). The resulting composite shows significantly enhanced water and CO2 adsorption properties compared to the parent MOF and the composite synthesized without the double solvent method.